2004
DOI: 10.1021/ja031792a
|View full text |Cite
|
Sign up to set email alerts
|

P-Chirogenic Diaminophosphine Oxide:  A New Class of Chiral Phosphorus Ligands for Asymmetric Catalysis

Abstract: We successfully synthesized a novel P-chirogenic diaminophosphine oxide 4, which was applied to catalytic enantioselective construction of quaternary carbon centers using Pd-catalyzed asymmetric allylic substitution with various beta-keto esters (up to 99% yield, 94% ee). Preliminary mechanistic studies indicated that two molecules of 8 coordinate to the Pd metal in a monodentate fashion, resulting in the formation of Pd complex 9 (Pd:8 = 1:2), which functions as the active species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(47 citation statements)
references
References 21 publications
0
45
0
2
Order By: Relevance
“…After concentration in vacuo, the obtained residue was purified by flash column chromatography (SiO 2 , hexane/AcOEtϭ4/1 to 1/1) to give (S,R P )-9a (213.1 mg, 27% yield) and (S,S P )-9b (431. 8 2 (1.1 mg, 0.003 mmol), (S,S P )-9b (3.3 mg, 0.006 mmol) in CH 2 Cl 2 (1 ml) at room temperature was added BSA (222 ml, 0.90 mmol). After being stirred for 10 min at the same temperature, a CH 2 Cl 2 solution of 11 (76.0 mg, 0.30 mmol in 0.5 ml of CH 2 Cl 2 ) and dimethyl malonate (103 ml, 0.90 mmol) were added successively to the reaction at 4°C.…”
Section: Compound (Sr P )-9a and (Ss P )-9bmentioning
confidence: 99%
See 1 more Smart Citation
“…After concentration in vacuo, the obtained residue was purified by flash column chromatography (SiO 2 , hexane/AcOEtϭ4/1 to 1/1) to give (S,R P )-9a (213.1 mg, 27% yield) and (S,S P )-9b (431. 8 2 (1.1 mg, 0.003 mmol), (S,S P )-9b (3.3 mg, 0.006 mmol) in CH 2 Cl 2 (1 ml) at room temperature was added BSA (222 ml, 0.90 mmol). After being stirred for 10 min at the same temperature, a CH 2 Cl 2 solution of 11 (76.0 mg, 0.30 mmol in 0.5 ml of CH 2 Cl 2 ) and dimethyl malonate (103 ml, 0.90 mmol) were added successively to the reaction at 4°C.…”
Section: Compound (Sr P )-9a and (Ss P )-9bmentioning
confidence: 99%
“…These preligands have been successfully applied to Pd-and Ir-catalyzed asymmetric allylic substitution reactions. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Detailed investigations into the reaction mechanism using a Pd-catalyzed asymmetric allylic alkylation of 1,3-diphenylallyl acetate with dimethyl malonate revealed that complex 3 [Pd-2 (1 : 2) complex] was the active catalyst. 9) With this result in hand, we became interested in the development of bidentate P-chiral diaminophosphine oxide preligands with an achiral diphenylphosphine moiety as the second coordinating group.…”
mentioning
confidence: 99%
“…30). 29) Catalytic enantioselective construction of a quaternary carbon center is a formidable challenge in organic synthesis. [32][33][34][35] Pd-catalyzed asymmetric allylic substitution using prochiral nucleophiles is one of the most straightforward approaches toward this end.…”
Section: Pd-catalyzedmentioning
confidence: 99%
“…28) 1. Design and Synthesis of P-Chirogenic Diaminophosphine Oxides: DIAPHOXs 29) Cyclic diaminophosphine oxides with a stereogenic center on the phosphorus atom can be prepared from chiral (or achiral) asymmetric diamines. Separation of the diastereomeric (or enantiomeric) mixture, however, is necessary to obtain optically pure P-chirogenic diaminophosphine oxide.…”
Section: Introductionmentioning
confidence: 99%
“…From a drug discovery perspective, this method provides access to useful building blocks with a single quaternary stereocenter. [53,54] …”
Section: Introductionmentioning
confidence: 99%